NASH: evaluation and treatment - Sanyal, Arun J. (Henry Stewart Talks, 2019)
NAFLD as a global problem and driver of liver-related burden of disease, Managing NAFLD in 3 simple steps, Diagnostic accuracy and performance (CAP), Increased risk of mortality by fibrosis stage, Restoring health for patients with NAFLD, Key concepts in approach to treatment of NASH, Various therapeutic options & clinical trials for treatment of NASH